2019
DOI: 10.9734/jerr/2019/v7i416976
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Solids Removal in Waste Stabilization Ponds

Abstract: Waste generation at Nigerian slaughterhouses poses a serious threat to the environment because of poor handling practices which results into adverse impact on land, air and water. The aim of this research is studying the dynamics of solid removal in waste stabilization pond at different hydraulics retention times (HRT). The characteristics of wastewater in Kwata slaughterhouse were 991 mg/l, 3427 mg/l and 4419 mg/l. For total suspended solids (TSS), total dissolved solids (TDS) and total solids (TS) respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The overall removal efficiency was 18.8%, lower than what was reported by Nwankwo et al . (2019) which were 91 and 96% for their study on the dynamics of solids removal in waste stabilisation ponds. Final effluent concentration was 462 ± 101 mg L −1 and within the limit of 4000, 1000, 1000, 2000, and 2000 mg L −1 of discharges into public sewer, perennial rivers, ephemeral stream, and other environments, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The overall removal efficiency was 18.8%, lower than what was reported by Nwankwo et al . (2019) which were 91 and 96% for their study on the dynamics of solids removal in waste stabilisation ponds. Final effluent concentration was 462 ± 101 mg L −1 and within the limit of 4000, 1000, 1000, 2000, and 2000 mg L −1 of discharges into public sewer, perennial rivers, ephemeral stream, and other environments, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorbtion is among the effective, easy and efficient techniques used for removing toxic metals from water sources (Suguna, Nadavala, Vudagandla, Boddu, and Aburi, 2017). The adsorption activity has been reported by (Kwaghger and Ibrahim, 2013), it is also used in pharmaceutical industry and in research laboratories as decolorizing agent and catalyst support (Yaumi, Mustafa;Isah;Babagana, and Ojih, 2015) and in medicine for adsorption of harmful chemicals and drugs (Nwankwo, Nwaiwu & Nwabanne (2018).…”
Section: Introductionmentioning
confidence: 93%
“…They also reported that Chlorella, Euglena, Scenedermus, and Microcystis are the predominant algae species found in the WSP systems. The drawbacks of WSP are their long hydraulic retention time ranging from 20 to 30 days, high water losses due to evaporation, and high dependency of such open systems process to the environmental factors like temperature, light intensity and risk of contamination (Nwankwo et al 2019). Over time, the sludge generation in ponds increases leading to lowering the mean residence retention time or contact time that results in decrease of contaminant removal and therefore significantly affect the pond microbial dynamics results in decreasing efficiency (Coggins et al 2019).…”
Section: Open Pondsmentioning
confidence: 99%